2012
DOI: 10.1371/journal.pone.0035540
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Cutaneous Oncoprotein HPVE6 by wtp53, Mutant p53R248W and ΔNp63α is HPV Type Dependent

Abstract: UV exposure and p53 mutations are major factors in non-melanoma skin cancer, whereas a role for HPV infections has not been defined. Previous data demonstrated the wtp53-mediated degradation of cutaneous HPV20E6 by caspase-3. ΔNp63α and hot-spot mutant p53R248W conveyed a protective effect on HPV20E6 under these conditions. We demonstrate a differential regulation by wtp53 of the E6 genes of cutaneous types HPV4, HPV5, HPV7, HPV27, HPV38, HPV48, HPV60 and HPV77. Caspase- or proteasome-mediated down-regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…However, this finding was not confirmed when E6/E7 was expressed in HaCat keratinocytes (54). It has been demonstrated that wt p53 induces the downregulation of E6 from HPV5, HPV20, and HPV38 (55), supporting the notion of a role for E6 in oncogenesis. In organotypic cultures of betaHPVs, E6 and E7 cause a delay in differentiation and altered keratinocyte growth (56,57).…”
Section: Discussionmentioning
confidence: 91%
“…However, this finding was not confirmed when E6/E7 was expressed in HaCat keratinocytes (54). It has been demonstrated that wt p53 induces the downregulation of E6 from HPV5, HPV20, and HPV38 (55), supporting the notion of a role for E6 in oncogenesis. In organotypic cultures of betaHPVs, E6 and E7 cause a delay in differentiation and altered keratinocyte growth (56,57).…”
Section: Discussionmentioning
confidence: 91%
“…However, HPV 20 has been shown to upregulate the p16INK4a and Akt–PI3K pathway, interfering with the cell cycle involved in progression to basal cell carcinoma. It is also known that the E6 proteins of HPV 20 can prevent UV-treated keratinocytes from undergoing apoptosis, while HPV38 E7 can degrade pRb increasing the lifespan of human keratinocytes by deregulating the cell cycle . In addition, the activation of nuclear factor kappa beta is believed to protect β-HPV immortalized human keratinocytes against tumor necrosis factor (TNF) and UV-mediated apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic activities of the E6 and E7 proteins includes p53 sequestration, pRB binding, interference with DNA damage response pathways, disruption of cell cycle and cell division pathways, and immune evasion (reviewed in 5 51 102 ). An oncogenic role for some betapapillomaviruses such as HPV5 and HPV8 includes important co-factors such as UV-damage and include p53 modulation 65 103 . Untreated HPV-associated cancers can progress to malignant cancers that are locally invasive, difficult to treat, and often lead to death of the host.…”
Section: Pathology/symptomatologymentioning
confidence: 99%
“…The oncogenic potential of members of the betapapillomaviruses are hypothesized to require co-factors including UV light and p53 polymorphisms 123 . The roles of the viral oncogenes in these instances include activation of telomerase and extension of cell life span via E6 124 , and a potential cancer correlation with E6 and polymorphisms in p53 103 123 .…”
Section: Epidemiology Incidence and Prevalencementioning
confidence: 99%